Spin dictators he changing face of tyranny in the 21st century - Seskuria, Natia (Oxford Princeton University Press, 2022)
Hitler, Stalin, and Mao ruled through violence, fear, and ideology. But in recent decades, a new breed of media-savvy strongmen has been redesigning authoritarian rule for a more sophisticated, globally connected world. In place of overt mass repression, rulers such as Vladimir Putin, Recep Tayyip Erdogan, and Viktor Orbǹ control their citizens by distorting information and simulating democratic procedures. Like spin doctors in democracies, they spin the news to engineer support. Uncovering this new brand of authoritarianism, Sergei Guriev and Daniel Treisman explain the rise of such "spin dictators", describing how they emerge and operate, the new threats they pose, and how democracies should respond.
Includes Index
Keywords: International relations--Periodicals; World politics--Periodical